MODEL OF INTERACTION BETWEEN FUSARIUM OXYSPORUM FUNGUS AND BANANA PLANTS - Aprilia Chandra, Cindy
Fusarium wilt disease is caused by the fungus Fusarium oxysporum f.sp. cubense (Foc) and can affect various types of plants, including banana plants. The Fusarium fungus produces Chlamydospore spores that can transmit disease to plants. Spore dispersal can occur through irrigation water, wind, and contaminated farming tools. This highly damaging disease can decrease banana plant production and pose a threat to food security worldwide. In this Final Project, a mathematical SEIR model is constructed to depict the dynamics of Fusarium disease spread in banana plants, followed by an analysis of critical points and stability. To test the model and understand the impact of the used parameters, numerical simulations are conducted. The spread of the Fusarium disease is found to be most influenced by the rate of contact between Susceptible plants and Chlamydospores in the soil. Additionally, if there are still Exposed and Infected banana plants cultivated by farmers, the spread of Fusarium disease will continue.